On the Energy Efficiency of NOMA for Wireless Backhaul in Multi-Tier Heterogeneous CRAN - Tran, Huu Q. (2019)
This paper addresses the problem of wireless backhaul in amulti-tier heterogeneous cellular network coordinated by a cloud-based central station(CCS), namely heterogeneous cloud radio access network (HCRAN). A non-orthogonal multiple access(NOMA) is adopted in the power domain for improved spectral efficiency and network through put of the wireless downlink in the HCRAN. We first develop a power allocation for multiple cells of different tiers taking account of the practical power consumption of different cell types and wireless backhaul. By analyzing the energy efficiency(EE) of the NOMA for the practical HCRAN downlink, we show that the power available at the cloud,the propagation environment and cell types have significant impacts on the EE performance. In particular,in a large network,the cells located at the cloud edge are shown to suffer from a very poor performance with a considerably degraded EE,which accordingly motivates us to propose an iteration algorithm for determining the maximal number of cells that can be supported in the HCRAN